100 First things that go - Sirett,Dawn (London DK Publishing, 2019)
Help little ones learn first words and build vocabulary with this things that go baby book that's filled with cars, trucks, planes, boats, tractors, and diggers. Favourite vehicles are clearly labelled on every page, and the exciting photos combined with fun illustrations provide lots to talk about, learn about, and smile about
Keywords: General knowledge book